2007
DOI: 10.1007/s10832-007-9024-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen permeability, stability and electrochemical behavior of % MathType!Translator!2!1!AMS LaTeX.tdl!TeX -- AMS-LaTeX! % MathType!MTEF!2!1!+- % feaaeaart1ev0aaatCvAUfeBSjuyZL2yd9gzLbvyNv2CaerbbjxAHX % garmWu51MyVXgatuuDJXwAK1uy0HwmaeHbfv3ySLgzG0uy0Hgip5wz % aebbnrfifHhDYfgasaacH8qrps0lbbf9q8WrFfeuY-Hhbbf9v8qqaq % Fr0xc9pk0xbba9q8WqFfea0-yr0RYxir-Jbba9q8aq0-yq-He9q8qq % Q8frFve9Fve9Ff0dmeaabaqaciGacaGaaeqabaWaaeWaeaaakeaaci % GGqbGaaiOCamaaBaaaleaacaaIYaaabeaakiaab6eacaqGPbGaae4t % amaaBaaaleaacaaI0aGaey4

Abstract: The high-temperature electronic and ionic transport properties, thermal expansion and stability of dense Pr 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 37 publications
6
53
1
Order By: Relevance
“…Promising electrochemical properties of the PNO end member (x = 2.0) are undermined by poor chemical stability at elevated temperatures corresponding to SOFC operating conditions. [10][11][12][13][14]18 The monoclinic distortion and supercell ordering seen at ambient temperature here may therefore reflect a highly strained structure that readily decomposes to more thermodynamically stable compositions.…”
Section: Structure and Property Trends In La2-xprxnio4+δmentioning
confidence: 85%
See 1 more Smart Citation
“…Promising electrochemical properties of the PNO end member (x = 2.0) are undermined by poor chemical stability at elevated temperatures corresponding to SOFC operating conditions. [10][11][12][13][14]18 The monoclinic distortion and supercell ordering seen at ambient temperature here may therefore reflect a highly strained structure that readily decomposes to more thermodynamically stable compositions.…”
Section: Structure and Property Trends In La2-xprxnio4+δmentioning
confidence: 85%
“…Under oxidizing atmospheres at elevated temperatures, it has been shown that Pr2NiO4+δ can decompose to a mixture of Pr4Ni3O10, PrNiO3-δ, and PrOx. [10][11][12][13][14] For this reason, there has been recent interest in mixed PNO-LNO compositions which could offer a compromise of chemical stability and electrochemical performance. [15][16][17][18][19] However, despite investigations spanning three decades, the phase diagram of the La2-xPrxNiO4+δ system; as a function of composition, oxygen stoichiometry, and temperature, is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The interface between LWO and PrN is good with no sign of crack or delamination. According to the thermal expansion coefficients (TEC) reported in literature, Pr 2 NiO 4 has a TEC close to that of LWO at temperature below 970 K but with a significant gap at temperature above 970 K (TEC LWO(300-1073 K) = 11 × 10 -6 (300-1073 K) [1]; TEC PrN(300-970 K) = 13.11 × 10 -6 K -1 , TEC PrN(970-1220 K) = 20.11 × 10 -6 K -1 ) [13]. The Figure 5 presents the total conductivity of the LWO electrolyte assuming that Rs is mainly due to LWO and taking into account the geometrical factors of the electrolyte dense pellets for the cells fired at 800, 1100, and 1200°C.…”
Section: Influence Of the Firing Temperaturementioning
confidence: 97%
“…17 Kilner et al used tracer diffusion and molecular simulation techniques for the study of oxygen diffusivity in La 2 NiO 4 -based oxide and confirmed that the fast oxygen diffusivity is observed along the rocksalt plane. 19,20 In our previous study, we reported the large oxygen permeation rate in Pr 2 NiO 4 doped with Cu and Ga. [21][22][23] The oxygen permeability of these oxides was studied by Kovalevsky et al 24 Neutron diffraction analysis suggests that interstitial oxygen in the rocksalt block is the main diffusing species in this oxide. 25,26 Although Pr deficiency is useful for achieving the high oxygen permeation rate in Pr 2 NiO 4 , 22 this effects have not been studied in detail.…”
mentioning
confidence: 91%